Origin of Abyssal NW Atlantic Water Masses Since the Last Glacial Maximum. Issue 5 (31st May 2018) - Pöppelmeier, F.; Gutjahr, M.; Blaser, P.; Keigwin, L. D.; Lippold, J.
Abstract: The notion of a shallow northern sourced intermediate water mass is a well evidenced feature of the Atlantic circulation scheme of the Last Glacial Maximum (LGM). However, recent observations from stable carbon isotopes (δ 13 C) at the Corner Rise in the deep northwest Atlantic suggested a significant contribution of a Northern Component Water mass to the abyssal northwest Atlantic basin that has not been described before. Here we test the hypothesis of this northern sourced water mass underlying the southern sourced glacial Antarctic Bottom Water by measuring the authigenic neodymium (Nd) isotopic composition from the same sediments from 5, 010‐m water depth. Neodymium isotopes act as a semiconservative water mass tracer capable of distinguishing between Northern and Southern Component Waters at the northwest Atlantic. Our new Nd isotopic record resolves various water mass changes from the LGM to the early Holocene in agreement with existing Nd‐based reconstructions from across the west Atlantic Ocean. Especially pronounced are the Younger Dryas and Bølling‐Allerød with unprecedented changes in the Nd isotopic composition. For the LGM we found Nd isotopic evidence for a northern sourced water mass contributing to abyssal depths, thus being in agreement with previous δ 13 C data from Corner Rise. Overall, however, the deep northwest Atlantic was still dominated by southern sourced water, since we found signatures that are intermediate between northern and southern end member compositions. Furthermore, this new record indicates that C and Nd isotopes were partly decoupled, pointing to nonconservative behavior of one or more likely of both water mass proxies during the LGM. Key Points: Deglacial ocean circulation changes were recorded with εNd in high resolution at the abyssal Corner Rise Distinct contribution of Northern Component Water is detectable at the abyssal northwest Atlantic during the Last Glacial Maximum The δ 13 C and εNd are partly decoupled at Corner Rise, implying nonconservative behavior of one or both proxies